E-037 Computational modeling for the pre-treatment planning of flow diverting stents. (22nd July 2018) - Chong, B; Bendok, B; Krishna, C; Sattur, M; Brown, B; Tawk, R; Miller, D; Rangel-Castilla, L; Lanzino, G
Abstract : Introduction: Sizing flow diverters (FDs) can be challenging during cerebral aneurysm pre-treatment planning. FDs can differ from their labelled lengths by 30% after deployment because of changes in vessel curvature and diameter. 1 Current FD sizing tools do not account for vessel shape or predict device apposition. We present a pilot study to evaluate the use of computational modelling for FD sizing. The modelling software is based on the finite element approach and has been shown to simulate FD deployments that closely match clinical deployments. 2 Methods: Twenty-four patient cases in three hospitals were selected for treatment with the pipeline embolization device. Twelve of the cases were pre-planned using the SurgicalPreView computational modeling software, while the remaining cases were conventionally planned. In the computationally modeled cases, each patient's CT image data were uploaded to SurgicalPreView and re-constructed before treatment. The principal physician simulated deployment of 1–3 different FDs on the software and evaluated simulation results before treatment. After treatment, the physician filled out a questionnaire on the usefulness of the simulation results. Further, post-treatment image data for the 12 cases were used to compare simulated and clinical deployments. Results: According to physician responses, computational modeling was useful for all cases and it improved confidence in device selection. In 58% of cases, simulation results changed the physician's original device selection. In most cases, the physician selected a longer length device or a larger device diameter after evaluating simulation results. Limited effect was observed on operative time and the number of endovascular devices used. An example comparison between simulated and clinical deployments is shown in figure 1. Conclusion: Overall, the pilot study showed improvements in FD pre-treatment planning using computational modeling. Simulation results helped physicians predict the behavior of FDs in tortuous vessels and with maximizing apposition. Pretreatment planning may reduce costs by shortening operative time and reducing the number of devices used. Improvements to FD selection can potentially lead to better patient outcomes. References: Fernandez H, Macho J, Andaluz J, Serra L, Larrabide I. Braided device foreshortening. presented at the Computer Assisted Radiology and Surgery, 2014. Babiker H, et al. Clinical validations of simulated neurovascular braided stent deployments . presented at the Frontiers in Medical Devices Conference – Innovations in Modeling and Simulation: Patient-Centered Healthcare, Washington, DC, 2016. Disclosures: B. Chong: 4; C; Endovantage LLC. B. Bendok: None. C. Krishna: None. M. Sattur: None. B. Brown: None. R. Tawk: None. D. Miller: None. L. Rangel-Castilla: None. G. Lanzino: None.